INFORMATIONAL UPBRINGING IN THE CONTEXT OF DEVELOPMENT OF A FUTURE TEACHER’S PROFESSIONAL PERCEPTION OF THE WORLD - Lodatko, Eugene; Yarygina, Nelya (Вісник Черкаського національного університету імені Богдана Хмельницького. Серія: "Педагогічні науки", 2016)
Introduction. The paper covers the rationale for the significance of informational upbringing of the students in the context of information development of the social and cultural space as a precondition for the formation of a future teacher professional worldview. The priority of the research is the study of various aspects of the worldview formation of a teacher in the context of modern information reality and the understanding of prerequisites for the interrelation of professional perception of the world of a future teacher with his informational upbringing. Purpose. The goal of research depends on the contradictions between the actual teaching practice and the (development) of capability of a teacher for various types of intellectual activity, as well as the professional perception of the world. The authors prove the increase of requirements for the professional worldview ensuring the adequateness of sensing and critical assessment of information, its influence on a future teacher professional development in the context of the information relations activization, the transition to new educational paradigm and the development of critical thinking. Methods. The research was based on the analysis of statistical sources concerning the information support of the social and cultural processes and the group social relations; the results of educational research discourse of the essence of a teacher’s professional worldview, the informational upbringing of a future teacher; the synthesis of teachers’ professional preferences in the information resources application. Results. The statement that professional perception of the world cannot be formed outside the process of educational activity being the informational by its nature is important to understand the processes taking place in the educational space. That is why the social and cultural effects resulting from the society information development should inevitably influence the organization and the meaning of this activity being fixed in the form of personal teaching experience. The experience gained in such manner makes up the foundations for deepening and extension of professional worldview of a teacher and enables the improvement of educational activities interpreted by the categories of pedagogical excellence. Professional worldview of a teacher is interpreted as the general vision, perception and understanding of the essence of social and cultural phenomena and the purpose of activity in cultural outlooks reflecting the value orientation and the educational purposes in their content (subject) implementation. While working on the paper, the authors pointed out and understood various aspects of professional activity of a teacher concerned with the use of modern information resources and services, and gave the reasons for the necessity of development of moral and ethical filters, able to ensure the adequateness of sensing and critical assessment of the information influencing the professional perception of the world of a teacher. Originality. The scientific novelty of the research, the results of which are detailed in the paper, is governed by the identifying of social, cultural and information specificity of the worldview development of a teacher in the context of modern information reality and the argumentation of the necessity of informational upbringing of a future teacher in the context of social communications and interaction with various information resources. Conclusion. The results of the analysis give reason to believe that the informational upbringing should be positioned for teachers, as the informational relations actors, to be one of the most important tasks of modern pedagogical science. That is why the creation of pedagogical system focused on the informational upbringing of a future teacher and promoting the formation of professional perception of the world, the efficient development of information relations and the ensuring of personal information security is the important project of the nearest future.